PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING LABORATORY TERHADAP KEMAMPUAN BERPIKIR KRITIS FISIKA SISWA DI MAN 2 BANYUWANGI - Arif Rahman Fadli; Subiki Subiki; Sri Astutik (FKIP Universitas Jember, 2019)
The problem solving laboratory model was a learning model that can train students in solving problems of physics concepts which is one component in training students' critical thinking skills. The purpose of this study was to examine the effect of Model Problem Solving Laboratory on students' critical thinking skills in Islamic Senior High School 2 Banyuwangi. This type of research was experimental research. Determination of the place of research using the purposive sampling area technique. The sample of this study was class X MIPA 1 and X MIPA 5. The design of this study used the Posttest-Only Control Group Design. Data collection techniques in this study were post-tests conducted at the end of the study. The Independent Sample T-Test test with the help of SPSS-23 was used as a method of analyzing critical thinking skills. The post-test average value of the critical thinking of the control class was 49.02, while the experimental class value was 65.25. Based on the results of data analysis of students' critical thinking skills using the independent sample t-test, concluded that there was an influence of the Learning Model Problem Solving Laboratory on Students' Critical Thinking Ability on physics at Islamic Senior High School 2 Banyuwangi..Key word: critical thinking skills, physics learning, problem solving laboratory.